Fatal Early-onset Sepsis Caused by Intrauterine Transmission of Serogroup Y Meningococcus. Issue 12 (28th September 2022) - Achten, Niek B.; Been, Jasper V.; Schoenmakers, Sam; Vermont, Clementien L.; Verdijk, Robert M.; Reiss, Irwin K. M.; Taal, H. Rob
Abstract : Infections by meningococcal species are extremely rare in the first days of life. We present a fatal case of early-onset sepsis presenting at birth, caused by intrauterine transmission of serogroup Y N. meningitidis, evidenced clinically and histologically by corresponding chorioamnionitis and N. meningitidis -positive amniotic fluid. This case confirms a long-standing suspicion that N. meningitidis can be transmitted in utero.